Three new and exceptional Damarchus species from Thailand (Araneae: Bemmeridae) - Schwendinger, Peter J.; Hongpadharakiree, Komsan (Zootaxa, 2023)
Damarchus pylorus sp. nov., D. lanna sp. nov. and D. dao sp. nov. are described from males and females collected in western and northern Thailand. Damarchus pylorus sp. nov. and D. lanna sp. nov. are morphologically unique within the genus by males having a para-embolic apophysis and a keel composed of coarse laminae on the lower (posterior) side of the palpal organ, and by females having sperm receptacles, composed of a strongly sclerotized base and an unsclerotized head, situated on the ventral side of a relatively long genital atrium. The distantly related D. dao sp. nov. is distinguished from all other congeners by males having a tibia I coupling spur with three megaspines. Presumed relationships of these three species and of the genus Damarchus are discussed. Information on biology and burrow structures of the new species is provided. Damarchus pylorus sp. nov. stands out by plugging the side shaft of its burrow with a soil pellet; similar plugging devices in unbranched burrows are known from other spider families.